A Study of Key Factors in the Introduction of RFID into Supply Chains through the Adaptive Structuration Theory - Wu, Mei Ying; Ku, Chun Wei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Since 2003, the Radio Frequency Identification System (RFID) technology has gained importance and has been widely applied. Numerous statistics indicate a high potentiality for RFID development in the near future.This study focuses on the issues derived from RFID technology and explores the impact of its introduction into supply chains. Based on the framework of the Adaptive Structuration Theory (AST), a questionnaire is designed for collecting research data, and Structural Equation Modeling (SEM) is adopted in order to identify the relationships among research constructs. The research findings indicate that technological features, promoters, and group cooperation systems of RFID have significant effects on the supply chain operation structure and indirectly influence factors of RFID introduction. It is evident from this study’s results that certain factors of RFID and a good supply chain operation structure have positive effects on the introduction of RFID into supply chains.